5‐Hydroxy‐isoxazolidine: A New Synthetic Approach to a Privileged Heterocycle for Organic Synthesis. Issue 18 (11th May 2020) - Presenti, Piero; Moiola, Mattia; Quadrelli, Paolo
Abstract: A modified pathway towards 5‐hydroxy‐isoxazolidines has been preliminarily investigated by taking advantage of the anti‐Markovnikov route in ene reactions of sterically encumbered nitrosocarbonyl intermediates in the presence of allylsilylethers. Fluoride‐mediated deprotection/cyclization of the ene adducts afforded the desired heterocycles in quantitative yields and the methodology is adaptable to a one‐pot procedure. Abstract : 5‐Hydroxy‐isoxazolidines has been preliminarily synthesized by taking advantage of the anti‐Markovnikov route in ene reactions of sterically encumbered nitrosocarbonyl intermediates in the presence of allylsilylethers. Fluoride‐mediated deprotection/cyclization of the ene adducts afforded the desired heterocycles in quantitative yields.